Measuring lateropulsion following stroke: A feasibility study using wii balance board technology - Birnbaum, M.; Brock, K.; Clark, R.; Hill, Keith (New Zealand Society of Physiotherapists, 2018)
The aim of this pilot study was to determine the feasibility and utility of using Wii Balance Board-derived centre of pressure data as measures of balance in people with lateropulsion following stroke. Ten individuals with lateropulsion, between one and twelve weeks post stroke, participated in this study. Participants were assessed on four occasions over a two-week period, performing a number of tasks sitting and standing on the Wii Balance Board, in addition to clinical measures. Feasibility was determined by participant retention and the percentage of testing occasions ceased prematurely. Clinical utility was explored through visual analysis of the Wii Balance Board-derived data. Participant retention was 100%. Cessation of testing due to discomfort or fatigue occurred 20% of the time. For the static balance tasks, mediolateral amplitude emerged as a variable of interest. Wii Balance Board-derived centre of pressure data from static sitting and standing tasks appeared to capture useful information about individuals with varying degrees of lateropulsion and displayed change over time. The use of Wii Balance Board technology as a measure for balance in individuals with lateropulsion appears feasible. A larger measurement study is required to establish the reliability and validity of this technology in this important clinical sub-group.